Ultrasound Muscle Assessment and Nutritional Status in Institutionalized Older Adults: A Pilot Study - Mateos-Angulo, Álvaro; Galán Mercant, Alejandro; Cuesta-Vargas, Antonio (MDPI, 2019)
Muscle thickness, measured by ultrasonography, has been investigated for nutritional assessment in older adults, however the associations between muscle ultrasound parameters in the lower limb and nutritional status have not been studied. The aim of this study was to investigate the relationship between muscle thickness echo intensity (EI), and nutritional status in home care residents. A cross sectional study was conducted involving 19 older adults from a home care in Malaga (Spain). We evaluated lower leg muscles by ultrasound, anthropometric data, physical function (measured by gait speed and the Short Physical Performance Battery), strength (handgrip and knee extensors strength) and nutritional status across the Mini-Nutritional Assessment Short-Form (MNA-SF). We found that muscle thickness assessed by ultrasonography independently predicts nutritional status by MNA-SF and after adjusting for handgrip strength or age and sex. As secondary findings, we found relations between strength, functional capacity and the MNA-SF test.
Keywords: Alimentación; Músculos - Tests; Aging; Functional capacity; Muscle thickness; Nutritional assessment; Ultrasound